Metaphysics - Theophrastus. (Mnemosyne, Supplements, 1993)
This book has been written from the conviction that general statements about the philosophical position taken by Theophrastus in this small but extremely difficult treatise, can only be made on the basis of a detailed interpretation of each and every sentence of the text. This resulted in a full commentary, which evades no philological or philosophical question that should be asked in order to elicit from the text a maximum of information. The outcome is a cautious but nonetheless explicit and determinate characterization and evaluation of Theophrastean metaphysics as a biologist's metaphysics, which deserves the attention of philosophers in its own right. The author has paid special attention to questions of Peripatetic idiom and terminology, thus increasing the value of this book to students of Peripatetic thought in general. The information brought together has been made easily accessible by full indexes.